1996
DOI: 10.1097/00000542-199611000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Isoflurane and Desflurane on Neurogenic Motor- and Somatosensory-evoked Potential Monitoring for Scoliosis Surgery

Abstract: Compared with cortical somatosensory-evoked potentials, neurogenic motor-evoked potential signals are well preserved in patients undergoing surgery to correct scoliosis under general anesthesia supplemented with isoflurane or desflurane in concentrations as great as 1 MAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Contrary to the major changes reported with 0.5% to 0.75% bupivacaine, with 2% mepivacaine and with 2% lidocaine [21][22][23], the somatosensory-evoked potentials were not modified. This finding was compatible with the respected electrical continuity of the spinal cord, although false negatives are possible [14,15]. The unchanged SCEPs, H-reflexes, and F waves observed during study conditions corresponded well to the explanations provided by Malmqvist et al [22], that SCEPs are unchanged because transmission of impulses from somatosensory-evoked potential stimulation through thick A fibers (Aα of motility and Aβ of sensation of vibrations) is unaffected by epidural analgesia.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Contrary to the major changes reported with 0.5% to 0.75% bupivacaine, with 2% mepivacaine and with 2% lidocaine [21][22][23], the somatosensory-evoked potentials were not modified. This finding was compatible with the respected electrical continuity of the spinal cord, although false negatives are possible [14,15]. The unchanged SCEPs, H-reflexes, and F waves observed during study conditions corresponded well to the explanations provided by Malmqvist et al [22], that SCEPs are unchanged because transmission of impulses from somatosensory-evoked potential stimulation through thick A fibers (Aα of motility and Aβ of sensation of vibrations) is unaffected by epidural analgesia.…”
Section: Discussionsupporting
confidence: 88%
“…An analysis time of 100 ms was used, and for each SCEP waveform, 300 to 1,000 sweeps were averaged twice. P40 latency and peak-to-peak amplitude (assessed between the onset of the wave and the positive peak) were determined [14,15].…”
Section: Electrophysiologic Recordingsmentioning
confidence: 99%
“…11,12 When inhalation anaesthetics were investigated, studies demonstrated that sevoflurane and isoflurane in particular depress the amplitudes of tcMEPs in a dose-dependent manner. 13,14 In a prospective study of Lo et al conducted with desflurane, one study group was administered desflurane anaesthesia, the other was applied TIVA (propofol), and both groups were also given morphine when required; in this study, the proper tcMEP responses were recorded in both groups. 15 In this method of tcMEP measurement, being different from the routine applications, they used 60% nitrous oxide in the desflurane group, and maintained the end-tidal concentration of desflurane between 3.4% and 4.3% .…”
Section: Resultsmentioning
confidence: 94%
“…A number of studies have shown that with partial neuromuscular blockade, effective monitoring could still be performed at 0.5 MAC, with more variability at 1.0 MAC. 3 With other, less disruptive options available, inhalational agents are generally to be avoided in cases requiring neurophysiological monitoring.…”
Section: Resultsmentioning
confidence: 99%